The importance of training for rural industrialisation - Taori Kamal
For a rapid and self-sustained development of rural areas, rural industrialisation is an essential ingredient which leads to the development of the entire economy. Since the economic activities in rural areas are exclusively in urban areas, the linkages, between rural-urban or agriculture industry are not strong and there is a wide gap between them. Rural industrialisation is only the effective means of reducing this imbalance and acclerating the process of rural development - Reproduced.
Keywords: Rural Industrialisation; Industry, Rural; Industrialisation; Training -- Industry, Rural